Distribution of Zakat, Infaq, and Shadaqa Funds to Poverty in Indonesia - Khoirunniswah, Qonita; Meylianingrum, Kurniawati; Mounadil, Abdelaziz (Maliki Islamic Economics Journal, 2023)
Poverty is an important problem that can affect the global economy, including Indonesia. The number of poverty in Indonesia is still very fluctuating, while the acquisition of zakah and infaq continues to increase from year to year. The main target in the distribution of zakah and infaq funds is to reduce to alleviate poverty. This study aims to determine the effect of zakah and infaq on poverty in Indonesia. This research uses quantitative methods with a descriptive approach. The data analysis used is multiple linear regression analysis. The results of this research showed that zakah had a significant negative influence on poverty. Infaq also has a significant negative effect on poverty. Simultaneously, zakah and infaq have a significant effect on poverty.